Oxidative Stress and Bronchopulmonary Dysplasia: Evidences From Microbiomics, Metabolomics, and Proteomics - Capasso, Letizia; Vento, Giovanni; Loddo, Cristina; Tirone, Chiara; Iavarone, Federica; Raimondi, Francesco; Dani, Carlo; Fanos, Vassilios (Frontiers in Pediatrics, 2019)
Bronchopulmonary dysplasia is one of the major issue affecting morbidity and mortality of surviving premature babies actually. Preterm newborns are particularly susceptible to oxidative stress and infants with bronchopulmonary dysplasia have a typical oxidation pattern in the early stages of this disease, suggesting the important role of oxidative stress in its pathogenesis. Bronchopulmonary dysplasia is a complex disease where knowledge advances as new investigative tools become available. The explosion of the “omics” disciplines has recently affected BPD research. This review focus on the new evidence coming from microbiomics, metabolomics and proteomics in relation to oxidative stress and pathogenesis of bronchopulmonary dysplasia; to clarify its pathogenesis yet not completely understood is a crucial point to set for the future efficacious prevention and treatment strategy.